1999
DOI: 10.1097/00002030-199910220-00020
|View full text |Cite
|
Sign up to set email alerts
|

Decreased morbidity and use of hospital services in English HIV-infected individuals with increased uptake of anti-retroviral therapy 1996-1997

Abstract: The observed reduction in new AIDS-defining events has led to a reduction in the need for inpatient hospital care and has been associated with an increased uptake of ART, including a switch to triple therapy. All of these factors are likely to have contributed to the observed reduction in mortality among English AIDS patients. As the overall uptake of ART remained relatively low in English centres further improvements can be anticipated. However, the medium to long-term effects of these treatment regimens will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
3
24
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Highly active antiretroviral therapy (HAART) has revolutionized the treatment of HIV leading to significant declines in HIV related morbidity and mortality as well as declines in hospitalization. [11][12][13][14][15][16][17] Although previous studies suggest that individuals with SMI are less likely to receive potentially life saving interventions for non-HIV-related chronic conditions, [18;19] few studies have evaluated the degree to which HIV infected individuals with SMI receive HAART. One study using New Jersey Medicaid claims data from 1996-1998 found that patients with serious mental illness were more likely to have initiated new antiretroviral therapy, defined as receiving a protease inhibitor or a non-nucleoside reverse transcriptase inhibitor, compared to those without serious mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Highly active antiretroviral therapy (HAART) has revolutionized the treatment of HIV leading to significant declines in HIV related morbidity and mortality as well as declines in hospitalization. [11][12][13][14][15][16][17] Although previous studies suggest that individuals with SMI are less likely to receive potentially life saving interventions for non-HIV-related chronic conditions, [18;19] few studies have evaluated the degree to which HIV infected individuals with SMI receive HAART. One study using New Jersey Medicaid claims data from 1996-1998 found that patients with serious mental illness were more likely to have initiated new antiretroviral therapy, defined as receiving a protease inhibitor or a non-nucleoside reverse transcriptase inhibitor, compared to those without serious mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…These cost figures convey strong policy implications to business decision making for employment strategies in developing countries.With the introduction of more effective antiretroviral therapies, a wide range of remarkable improvement has been observed in HIV/AIDS treatment outcomes, ranging from longer survival time and increased quality of life. In the meantime, the direct treatment costs have also changed substantially, resulting from the use of advanced antiretroviral therapies [33,34,35,36,37,38,39,40,41,42,43]. Therefore, following our modeling framework, further study will assess the incremental benefits and costs of advanced antiretroviral combination therapy in treating HIV-infected workers against the benchmark costs.…”
Section: Discussionmentioning
confidence: 99%
“…152 The National Prospective Monitoring survey has been used to assess intermediate outcomes such as viral load in HIV patients. 149 The UK Thalassaemia Register has been used to assess the outcomes of screening for affected couples. 162 Comparative audit was the most common role for clinical registers with around half being used for this purpose.…”
Section: Use In Ht Assessmentmentioning
confidence: 99%